AN EXPLORATION OF JUSTICE: IDEAL AND NONIDEAL THEORY PERSPECTIVES ON THE CONSTITUTION (The Pretoria Student Law Review, 2023)
This article explores and analyses the concept of justice in postapartheidSouth Africa and whether the 1996 Constitution of theRepublic of South Africa is just. This is done through critical analysisand juxtaposition of the varieties of justice presented by constitutionaloptimists and constitutional abolitionists. The paper will show how theprinciples of Ideal Theory and Non-Ideal Theory feature in the politicalnarratives of the constitutional optimists and abolitionists,respectively. Further, this paper allows for introspection surroundingthe conception of justice and how justice is realised in society. Finally,it will be argued that the conception of justice that manifests in societyis subjective to the interests of the agents that hold the economicmeans to influence political power.